Effect of netupitant, a highly selective NK1 receptor antagonist, on the pharmacokinetics of palonosetron and impact of the fixed dose combination of netupitant and palonosetron when coadministered with ketoconazole, rifampicin, and oral contraceptives - Calcagnile, Selma; Lanzarotti, Corinna; Rossi, Giorgia; Henriksson, Anders; Kammerer, Klaus Peter; Timmer, Wolfgang (Supportive care in cancer, 2013)
Objectives Neurokinin-1 receptor antagonists (NK 1 RAs) are commonly coadministered with a 5-HT 3 RA such as palonosetron to prevent nausea and vomiting induced by chemotherapy. Netupitant, a new highly selective NK 1 RA, is both a substrate for and a moderate inhibitor of CYP3A4. Three studies were designed to evaluate the potential drug–drug interaction of netupitant with palonosetron and of the fixed dose combination of netupitant and palonosetron, NEPA, with an inhibitor (ketoconazole), an inducer (rifampicin) and a substrate (oral contraceptives) of CYP3A4. Methods Study 1 was a three-way crossover in 18 healthy subjects receiving netupitant alone, palonosetron alone, and the combination of both antiemetics. Studies 2 and 3 were two-way crossover trials where healthy subjects received NEPA (the fixed dose combination of netupitant and palonosetron). In study 2, 36 subjects received NEPA alone (day 1) and in combination with ketoconazole or rifampicin. In study 3, 24 healthy women received ethinylestradiol/levonorgestrel alone or in combination with NEPA (day 1). Results There were no significant pharmacokinetic interactions between netupitant and palonosetron. Ketoconazole increased netupitant area under curve (AUC) by 140 % and C max by 25 %. Rifampicin decreased netupitant AUC by 83 % and C max by 62 %. NEPA did not significantly affect exposure to ethinylestradiol, while systemic exposure to levonorgestrel increased by 40 %, but this was not considered clinically relevant. Conclusions There were no clinically relevant interactions between netupitant and palonosetron, or between NEPA and oral contraceptives. The coadministration of NEPA with inhibitors or inducers of CYP3A4 may require dose adjustments. Treatments were well tolerated.